2020
DOI: 10.1002/jor.24580
|View full text |Cite
|
Sign up to set email alerts
|

Fibrotic changes in the infrapatellar fat pad induce new vessel formation and sensory nerve fiber endings that associate prolonged pain

Abstract: The infrapatellar fat pad (IFP) contains nerve fiber endings and is considered to play an important role in the perception of knee pain. However, it is unclear whether and to what degree prolonged pain influences the nociceptive role of the IFP. To answer this question, we established a novel rat model of knee pain in which inflammation is restricted to the IFP. Rats received a single intra‐IFP injection of monoiodoacetic acid (MIA) (0.2 mg/10 µL or 1.0 mg/10 µL) in the left knee and a phosphate‐buffered salin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 32 publications
2
20
0
Order By: Relevance
“…These findings might open the possibility that fibrosis could be the target of a novel therapeutic strategy to counteract the OA progression and related pain in OA patients. This is also supported by a recently published paper by Onuma et al that established a novel inflammation-induced knee pain model in rats and showed that the inflammation-induced fibrotic changes in the IFP were associated with the prolongation of joint pain [37]. The main limitation of our work is the age and BMI differences between the two groups of subjects, due to their specific categorization, given the fact that ACL rupture usually occurs in young, lean athletes, while OA occurs mainly in aging females.…”
Section: Discussionsupporting
confidence: 63%
“…These findings might open the possibility that fibrosis could be the target of a novel therapeutic strategy to counteract the OA progression and related pain in OA patients. This is also supported by a recently published paper by Onuma et al that established a novel inflammation-induced knee pain model in rats and showed that the inflammation-induced fibrotic changes in the IFP were associated with the prolongation of joint pain [37]. The main limitation of our work is the age and BMI differences between the two groups of subjects, due to their specific categorization, given the fact that ACL rupture usually occurs in young, lean athletes, while OA occurs mainly in aging females.…”
Section: Discussionsupporting
confidence: 63%
“…These studies should also address concomitant or subsequent changes in vascularity and innervation, which could conceivably contribute to changes in OA-related outcomes including pain and activity. 55 Together, our results show that fibrosis of the mouse knee driven by tibial compression displayed histological, cellular, and molecular features that mimic aspects of the human condition. We also found that early timepoints without established histological fibrosis had transcriptional changes consistent with a profibrotic phenotype, demonstrating that this model can be used to understand the mechanisms driving fibrosis and to test therapies to prevent the development of knee fibrosis.…”
Section: Discussionsupporting
confidence: 57%
“…CGRP is a neuropeptide released from C nerve bers and not only has a pain-transmitting action but also is involved in neuropathic in ammation. (28,29) The content of CGRP was determined according to previous studies about the concentration of CGRP in the knee joint. (30,31) Regarding CGRP related to MSCs, Zhang et al demonstrated that CGRP at 10 − 6 -10 − 9 M promoted migration of human umbilical cord MSCs and that CGRP was a key chemokine in the migration of umbilical cord MSCs to the spinal lesion site in rats.…”
Section: Discussionmentioning
confidence: 99%